88.5k views
0 votes
Y=x^2-6x+3 help write the vertex form of the equation

User Kumar D
by
6.4k points

1 Answer

3 votes

Answer:


y=(x-3)^2-6

Explanation:


y=x^2-6x+3

This is written in the standard form of a quadratic function:


y=ax^2+bx+c

where:

  • ax² → quadratic term
  • bx → linear term
  • c → constant

You need to convert this to vertex form:


y=a(x-h)^2+k

where:

  • (h,k) → vertex

To find the vertex form, you need to find the vertex. For this, use the equation for axis of symmetry, since this line passes through the vertex:


x=-(b)/(2a)

Using your original equation, identify the a, b, and c terms:


a=1\\\\b=-6\\\\c=3

Insert the known values into the equation:


x=-((-6))/(2(1))

Simplify. Two negatives make a positive:


x=(6)/(2) =3

X is equal to 3 (3,y). Insert the value of x into the standard form equation and solve for y:


y=3^2-6(3)+3

Simplify using PEMDAS:


y=9-18+3\\\\y=-9+3\\\\y=-6

The value of y is -6 (3,-6). Insert these values into the vertex form:


(3_(h),-6_(k))\\\\y=a(x-3)^2+(-6)

Insert the value of a and simplify:


y=(x-3)^2-6

:Done

User DirtyMind
by
6.5k points